2002
DOI: 10.1192/bjp.180.5.428
|View full text |Cite
|
Sign up to set email alerts
|

Mental health and the built environment: Cross – sectional survey of individual and contextual risk factors for depression

Abstract: The prevalence of depression was associated with independently rated features of the built environment, independent of individuals' socio-economic status and internal characteristics of dwellings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
216
2
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(236 citation statements)
references
References 19 publications
14
216
2
4
Order By: Relevance
“…From univariate analysis and the published literature (28)(29)(30)(31)34) , age, marital status, education, annual family income, religion and living alone were identified as possible confounders.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From univariate analysis and the published literature (28)(29)(30)(31)34) , age, marital status, education, annual family income, religion and living alone were identified as possible confounders.…”
Section: Methodsmentioning
confidence: 99%
“…Age, marital status, religion, living alone and highest qualification were the sociodemographic factors chosen a priori as they were believed to be related to both distress and diet based on previous literature (28)(29)(30)(31)(32)(33) . No information was collected on diagnosis or treatments for psychological disorders.…”
Section: Other Factorsmentioning
confidence: 99%
“…McKenzie et al (2002) argue that the social network mental disorders like schizophrenia. Weich et al (2002) consider the built environment, finding that deck-access and recently built housing are associated with depression. Weich et al (2005) also examined the importance of the household, finding similar levels of depression among cohabiting individuals.…”
Section: Mental Healthmentioning
confidence: 99%
“…Some literature exploring the relationship between the built environment do exist and found that residence in a built environment of poor quality is associated with a greater incidence of depression. 32, 33 Matheson and colleagues 23 also found residential mobility and material deprivation associated with depression. Poorer neighborhood conditions have also been related to higher stress levels.…”
mentioning
confidence: 99%